Mitochondrial Ncrna Targeting Induces Cell Cycle Arrest and Tumor Growth Inhibition of Mda-Mb-231 Breast Cancer Cells Through Reduction of Key Cell Cycle Progression Factors - Borgna-Christie, V (Nature Publishing Group, 2019)
The family of long noncoding mitochondrial RNAs (ncmtRNAs), comprising sense (SncmtRNA), and antisense (ASncmtRNA-1 and ASncmtRNA-2) members, are differentially expressed according to cell proliferative status; SncmtRNA is expressed in all proliferating cells, while ASncmtRNAs are expressed in normal proliferating cells, but is downregulated in tumor cells. ASncmtRNA knockdown with an antisense oligonucleotide induces massive apoptosis in tumor cell lines, without affecting healthy cells. Apoptotic death is preceded by proliferation blockage, suggesting that these transcripts are involved in cell cycle regulation. Here, we show that ASncmtRNA knockdown induces cell death preceded by proliferative blockage in three different human breast cancer cell lines. This effect is mediated by downregulation of the key cell cycle progression factors cyclin B1, cyclin D1, CDK1, CDK4, and survivin, the latter also constituting an essential inhibitor of apoptosis, underlying additionally the onset of apoptosis. The treatment also induces an increase in the microRNA hsa-miR-4485-3p, whose sequence maps to ASncmtRNA-2 and transfection of MDA-MB-231 cells with a mimic of this miRNA induces cyclin B1 and D1 downregulation. Other miRNAs that are upregulated include nuclear-encoded hsa-miR-5096 and hsa-miR-3609, whose mimics downregulate CDK1. Our results suggest that ASncmtRNA targeting blocks tumor cell proliferation through reduction of essential cell cycle proteins, mediated by mitochondrial and nuclear miRNAs. This work adds to the elucidation of the molecular mechanisms behind cell cycle arrest preceding tumor cell apoptosis induced by ASncmtRNA knockdown. As proof-of-concept, we show that in vivo knockdown of ASncmtRNAs results in drastic inhibition of tumor growth in a xenograft model of MDA-MB-231 subcutaneous tumors, further supporting this approach for the development of new therapeutic strategies against breast cancer. © 2019, The Author(s).